Lamotrigine Induced Erythema Multiforme: A Case Report - Iram, Mahvash; Rani. R.H, Shobha; Bhat.Y, Megha (Indian Journal of Pharmacy Practice)
The prototypical lesion of Erythema Multiforme is a targetoid dusky erythematous patch, found predominantly on the extremities, although many different morphologies may be observed. Lamotrigine is an anti epileptic drug found to be effective to treat bi polar disorder, however it is reported to cause various hypersensitivity reactions ranging from a simple rash to life threatening reactions like Steven Johnsons Syndrome. A case of Lamotrigine induced Erythema Multiforme is discussed herewith.
Keywords: Erythema Multiforme; Lamotrigine; Anti-epileptic drugs